Progress in Botany
DOI: 10.1007/3-540-27998-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation in clonal plants

Abstract: Ecological aspects of clonal growth have been reviewed by Dietz and Steinlein (2001). The present review focuses on the physiological aspects of clonal growth to elucidate the cost/benefit relationships in maintaining physical connections between foraging ramets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 168 publications
(184 reference statements)
0
9
0
Order By: Relevance
“…Stressors such as high salinities or low nutrient availability can prevent S. alterniflora from investing resources into new shoot production, particularly in the summer months (Smart andBarko 1980, Naidoo et al 1992). As with other plants occurring in stressful environments, S. alterniflora may invest in live leaf tissue maintenance as opposed to new leaf production, except when actively losing live leaf tissue (e.g., via grazing) (Smith and Smith 2001, Bortolus et al 2004, Lo¨tscher 2006. When live leaf tissue is lost to grazing, the plant is forced to invest in more costly new leaf production rather than tissue maintenance Smith 2001, Bortolus et al 2004).…”
Section: Facilitation Mitigates Top-down Control Of S Alternifloramentioning
confidence: 99%
“…Stressors such as high salinities or low nutrient availability can prevent S. alterniflora from investing resources into new shoot production, particularly in the summer months (Smart andBarko 1980, Naidoo et al 1992). As with other plants occurring in stressful environments, S. alterniflora may invest in live leaf tissue maintenance as opposed to new leaf production, except when actively losing live leaf tissue (e.g., via grazing) (Smith and Smith 2001, Bortolus et al 2004, Lo¨tscher 2006. When live leaf tissue is lost to grazing, the plant is forced to invest in more costly new leaf production rather than tissue maintenance Smith 2001, Bortolus et al 2004).…”
Section: Facilitation Mitigates Top-down Control Of S Alternifloramentioning
confidence: 99%
“…Clonal integration may improve the performance of clonal plants in harsh habitats by enabling translocation of resources between connected ramets (Alpert 1999;Alpert et al 2003;Lötscher 2006;Wang et al 2008;Yu et al 2008). In addition, vegetative multiplication allows clonal plants to spread extensively and establish ramets in new microhabitats Retuerto 2006b, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This unique characteristic of clonal plants is termed as physiological integration (Pitelka and Ashmun 1985;Alpert and Mooney 1986;Slade and Hutchings 1987;Alpert 1991). Many studies have shown that physiological integration facilitates establishing new ramets of offspring in clonal plants and further benefits the survival and growth of whole clone fragments Retuerto 2005, 2006;Lötscher 2006;Wang et al 2008;Li et al 2009). Thus, it has been proposed that in clonal plants species, physiological integration evolved as an adaptation to different conditions.…”
Section: Introductionmentioning
confidence: 98%